Antioxidant Activities of Crude Phlorotannins from Sargassum hemiphyllum - 赵智丽 杨小青 龚忠勤 潘明珠 韩雅莉 刘义 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
Brown algae are well known as a source of biologically active compounds, especially those having antioxidant activities, such as phlorotannins. In this study we examined the antioxidant activities of crude phlorotannins extracts（CPEs） obtained from Sargassum hemiphyllum（SH） and fractionated according to the molecular weights. When CPEs were administrated at a dose of 30 mg/kg to Kunming mice pre-treated with carbon tetrachloride（CCl4）, the levels of oxidative stress indicators in the liver, kidney and brain were significantly reduced in vivo. All the components of various molecular weight fractions of CPEs exhibited greater scavenging capacities in clearing hydroxyl free radical and superoxide anion than the positive controls gallic acid, vitamin C and vitamin E. Particularly, the components greater than 30 k D obtained from ethyl acetate phase showed the highest antioxidant capacities. These results indicated that SH is a potential source for extracting phlorotannins, the algal antioxidant compounds.